AB0787 Carotid artery plaques are associated with coronary atherosclerosis independent of several cardiovascular risk calculators in patients with inflammatory joint diseases (ijd). (23rd January 2014) - Rollefstad, S.; Ikdahl, E.; Olsen, I. C.; Kvien, T. K.; Eirheim, A. S.; Pedersen, T. R.; Semb, A. G.
Abstract : Background: Patients with rheumatoid arthritis and carotid plaques (CPs) have been shown to have an increased risk of future acute coronary syndrome. Objectives: To evaluate if CPs was associated with coronary atherosclerosis (CA) in patients with IJD. Methods: In a preventive cardio-rheuma clinic 157 patients with IJD were referred for CV risk evaluation. Traditional CV risk factors were recorded. All patients underwent B-Mode ultrasound of the carotid arteries for evaluation of CPs and multidetector computer tomography (MDCT) coronary angiography for evaluation of CA. Results: The presence of CPs was also comparable across the various IJD [RA, n= 76 (77.6%), AS: 36 (85.7%), PsA 15 (88.2%), p=0.38]. In logistic regression analyses CPs was significantly associated with CA (Table) independent of the 3 CV risk calculators: SCORE, Framingham and Reynolds. When number of CPs was added in the models (Table), this associations was further increased. There was no significant difference between the 3 IJD groups. Image/graph: Conclusions: CPs was associated with CA independent of CV risk calculators and can therefore be regarded as CV disease in patients with IJD. This observation has clinical implications in CV risk evaluation and prevention. Disclosure of Interest: None Declared